Factores sustanciales y procesales de la competencia de la Corte Penal Internacional frente al derecho interno (2013)
The scope of the factors establishing the jurisdiction of the international Criminal Court (iCC) are examined in this paper, taking into account the concept of admissibility versus internal features of a substantial, material and procedural nature. the factors in the construction of international justice that allowed for the creation of the iCC are analyzed in this sense, as are those providing for jurisdiction over the principles of domestic law, particularly Article 17 on admissibility, the repercussions on the factors determined by domestic crimes and the consequences with respect to the identity and exercise of jurisdiction in view of possible action in Colombia's internal system on the grounds of international responsibility.